Penerapan model pembelajaran make a match untuk meningkatkan pemahaman konsep kondisi geografis di Indonesia pada peserta didik kelas V sekolah dasar - Arti Dewi, Jois Ayu; Siti Poerwanti, Jenny Indrastoeti; Wahyuningsih, Siti; Kussriyani, Kussriyani (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of this research to improve understanding of the concept ofgeographical conditions in Indonesia through make a match model. The target of this research is grade 5 students at SD Negeri Tunggulsari II Surakarta in 2019. Classroom action research is conducted for two cycles. Totally, this school have 32 students at grade 5. Data collection techniques such as interview, observation, test, and documentation with using source and technique triangulation. The first cycle resulting in a percentage of 40,63% in classical, and the study continued with the second cycle with the percentage of 81,26% in classical terms. Based on the result of the research, it can be conclude that application make a match model can improved understanding of the concept Indonesian geography condition on 5th students of SD Negeri Tunggulsari II Surakarta in the 2019/2020 academic year .